Leadership Skills in Administrative Governance: Evidence from Lao PDR National Assembly - Khamkieo Phommavong (jfpublisher, 2026)
This study examines leadership skills across administrative levels within the National Assembly of Lao PDR through empirical validation of a three-dimensional competency framework. Employing quantitative methodology, the research surveyed 240 administrative leaders at committee, department, and division levels using stratified sampling to ensure proportional representation. Leadership skills were measured across conceptual, human, and technical dimensions using validated instruments with five-point Likert scales. Exploratory Factor Analysis confirmed strong internal consistency, with Kaiser-Meyer-Olkin value of 0.865 and significant Bartlett's test results indicating excellent sampling adequacy. Factor extraction explained 67.458% of total variance, validating three distinct categories: human skills (22.285% variance) encompassing motivation, ethics, adaptability, and interpersonal capabilities; technical skills (17.692% variance) including ICT proficiency, administrative competence, and specialized expertise; and conceptual skills (27.481% variance) comprising vision, political acumen, problem-solving, and decision-making. High communalities for vision (0.987), political skills (0.950), and motivation (0.835) underscore their critical importance for administrative effectiveness. Results demonstrate that leadership competencies function as integrated, interdependent dimensions rather than isolated abilities. The validated framework provides actionable guidance for targeted capacity-building programs, succession planning strategies, and institutional strengthening initiatives aligned with regional administrative development objectives. This research offers the first comprehensive empirical validation of skills-based leadership within Southeast Asian administrative contexts, contributing theoretical advancement while addressing practical governance challenges in developing democracies.